Human epidermal growth factor receptor targeted inhibitors for the treatment of ovarian cancer - Maria Bonello (Cancer Biology & Medicine, 2018)
Ovarian cancer is the second most lethal gynecological cancer worldwide and while most patients respond to initial therapy, they often relapse with resistant disease. Human epidermal growth factor receptors (especially HER1/EGFR and HER2/ERBB2) are involved in disease progression; hence, strategies to inhibit their action could prove advantageous in ovarian cancer patients, especially in patients resistant to first line therapy. Monoclonal antibodies and tyrosine kinase inhibitors are two classes of drugs that act on these receptors. They have demonstrated valuable antitumor activity in multiple cancers and their possible use in ovarian cancer continues to be studied. In this review, we discuss the human epidermal growth factor receptor family; review emerging clinical studies on monoclonal antibodies and tyrosine kinase inhibitors targeting these receptors in ovarian cancer patients; and propose future research possibilities in this area.